Multi-effect corrosion-inhibition functional anticorrosive filler, preparation method and multi-effect corrosion-inhibition anticorrosive coating

Through the preparation of fly ash-based composite multi-stage structure, the existing environmentally friendly anti-rust fillers have been solved inadequate performance in severe corrosion environments, and the development of multi-effect corrosion-inhibiting functional anti-corrosion fillers has been achieved, which significantly improves the anti-corrosion performance and interface compatibility of the paint.

CN119552529APending Publication Date: 2025-03-04天津大学浙江研究院
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411727309.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing environmentally friendly anti-rust fillers are difficult to protect metal substrates for a long time in severe corrosion environments, and the interface wettability with the resin matrix is ​​poor, affecting corrosion resistance.

Method used

By using fly ash as the main raw material, alkali activation treatment and mesoporous structure preparation are carried out to form a composite filler with ion exchange properties, and corrosion-inhibiting modification is performed on this basis to form a multi-level structure multi-effect corrosion-inhibiting functional corrosion-inhibiting anti-corrosion filler.

Benefits of technology

It significantly improves the ion exchange performance and corrosion inhibition ability of the filler, enhances the long-term anti-corrosion performance of the paint, improves the interface wettability between the filler and the resin matrix, and is suitable for metal substrate protection in severe corrosion environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552529A_ABST
    Figure CN119552529A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-effect corrosion-inhibition functional anticorrosive filler, a preparation method and a multi-effect corrosion-inhibition anticorrosive coating, and the method comprises the following steps: preparing an activated fly ash filler by an alkali roasting method, and simultaneously preparing a mesoporous metal oxide and doping metal elements in the process to obtain an activated fly ash composite filler precursor; the activated fly ash composite filler precursor is aged by using an activated dopant in an alkaline solution, and is crystallized in a hydrothermal reaction kettle to form the zinc-doped activated fly ash composite filler which shows excellent ion exchange performance. And treating the activated filler by using a corrosion inhibition modifier and an ion modifier through a one-pot method, and finally preparing the multifunctional composite anticorrosive filler through a vacuum impregnation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of coatings, and in particular relates to a multi-effect corrosion-inhibiting functional anticorrosive filler, a preparation method and a multi-effect corrosion-inhibiting anticorrosive coating. Background Art

[0002] Metal corrosion has caused a lot of economic losses and waste of resources. In recent years, corrosion has shown an expanding trend in some fields. With the further implementation of environmental protection policies, some anti-rust pigments containing heavy metals have been gradually eliminated, and a type of environmentally friendly anti-rust filler with ion exchange behavior has gradually entered people's field of vision, among which calcium ion exchange anti-corrosion fillers are the most concerned. Fly ash is a common solid waste generated by coal-fired power plants. Its potential volcanic ash activity has led to its widespread use in the field of concrete. It has a high specific surface area and can show a high hydration gel potential after simple treatment. Fly ash is an excellent carrier for the preparation of ion exchange anti-rust pigments.

[0003] In the prior art, conventional environmentally friendly anti-rust pigments on the market are difficult to meet the requirements of high corrosion environments. Conventional anti-rust fillers require a complex process to prepare porous gel materials as the basic carrier of ion exchange fillers, and their interface interaction with the coating matrix is ​​poor. In addition, the development of fly ash-based anti-rust fillers in coatings is very limited. Its internal porous structure and excellent hydration performance make it difficult to use in harsh corrosion environments. There are few functional anti-corrosion strategies and anti-corrosion mechanisms in the field of water-based coatings. The corrosion inhibition behavior of conventional anti-rust fillers on the market is very limited.

[0004] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention

[0005] The purpose of the present invention is to provide a multi-effect corrosion-inhibiting functional anti-corrosion filler, a preparation method and a multi-effect corrosion-inhibiting anti-corrosion coating, which can solve the problem that the corrosion inhibition performance of the environmentally friendly anti-rust filler in the prior art is poor.

[0006] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:

[0007] A multi-effect corrosion-inhibiting functional anti-corrosion filler, comprising a fly ash-based composite multi-level structure, which is obtained by using fly ash as a main raw material and at least undergoing activation pore formation, hydrothermal doping and loading;

[0008] The activated pore-forming step is to react fly ash, alkaline activator, metal oxide precursor and pore-forming agent as raw materials to obtain an activated fly ash-based precursor;

[0009] Hydrothermal doping is to obtain ion exchange composite fillers by hydrothermal reaction of activated fly ash-based precursor and zinc source;

[0010] The load is an ion exchange type composite filler, an ion modifier and a corrosion inhibitor modifier to obtain a fly ash-based composite multi-level structure.

[0011] In one or more embodiments of the present invention, the raw materials used for activation and pore formation include fly ash, alkali activator, pore former and metal oxide precursor in a weight ratio of (15-40): (15-50): (2-6): (10-20).

[0012] In one or more embodiments of the present invention, the raw materials used for hydrothermal doping include an activated fly ash precursor, a zinc source, and water in a weight ratio of (15-40):(8-16):(20-50).

[0013] In one or more embodiments of the present invention, the raw materials used for loading include an ion exchange composite filler, an ion modifier and a corrosion inhibitor modifier in a weight ratio of (3-8): (2-4): (1-2).

[0014] In one or more embodiments of the present invention, the metal oxide precursor is selected from cerium nitrate, zinc nitrate and iron nitrate.

[0015] In one or more embodiments of the present invention, the zinc source is selected from zinc chloride and zinc nitrate.

[0016] In one or more embodiments of the present invention, the ion modifier is selected from calcium oxide, calcium chloride, calcium nitrate and cerium nitrate.

[0017] In one or more embodiments of the present invention, the corrosion inhibitor modifier is selected from triisopropanolamine and ethylenediaminetetraacetic acid.

[0018] Another specific embodiment of the present invention provides a technical solution as follows:

[0019] A method for preparing a multi-effect corrosion-inhibiting functional anticorrosive filler comprises the following steps:

[0020] S1, using fly ash, a pore-forming agent, a metal oxide precursor, and water as raw materials, and using an alkaline activator to perform an alkali activation treatment on the fly ash to prepare an activated fly ash-based precursor;

[0021] S2, using an activated fly ash-based precursor, an activated dopant, and water as raw materials to perform a hydrothermal reaction to prepare an ion exchange composite filler;

[0022] S3. Using ion exchange composite fillers, ion modifiers and corrosion inhibitor modifiers as raw materials, a one-pot mixing reaction is carried out, and then vacuum impregnation is performed to obtain multi-effect corrosion inhibition functional anticorrosive fillers.

[0023] Another specific embodiment of the present invention provides a technical solution as follows:

[0024] A multi-effect corrosion-inhibiting and anti-corrosion coating comprises the multi-effect corrosion-inhibiting functionalized anti-corrosion filler.

[0025] Compared with the prior art, the present invention uses solid waste fly ash as a matrix, utilizes alkali activation treatment and mesoporous structure preparation technology to form a shell-core structure with ion exchange performance, and gradually loads corrosion-inhibiting metal ions and other elements during the mesoporous structure preparation process and the subsequent ion exchange process, and simultaneously performs organic grafting and inorganic impregnation passivation functional modifications to prepare a multifunctional corrosion-inhibiting functional filler, which is applied to the coating system to enhance the long-term anti-corrosion performance of the coating.

[0026] First, fly ash is treated with alkali activation and corrosion-inhibiting mesoporous metal oxides are prepared at the same time, which strengthens the adsorption of the composite filler to the medium and destroys the dense glass microsphere morphology of fly ash, which is conducive to the reconstruction of the structure into ion exchange filler.

[0027] Subsequently, the mixed structure was crystallized in a hydrothermal reactor, with the mesoporous metal oxide structure and the broken fly ash porous structure as growth sites, and zinc was introduced simultaneously to prepare a zinc-doped fly ash composite ion exchange filler. Zinc, which protects the metal substrate by sacrificial cathode method, and cerium, which has its own redox passivation effect, were introduced into the composite structure to enhance the ion exchange performance of the composite material.

[0028] Finally, a cation exchange experiment was carried out on the composite filler with strong ion exchange properties. The calcium ions and cerium ions with passivating film-type corrosion inhibition ions were loaded into the composite structure, and the corrosion inhibition aids with chelating effect were loaded therein by using organic modification and inorganic loading methods to form a functional filler with multi-level structure mixing and multi-effect corrosion inhibition. In this process, the interfacial wetting behavior between the filler and the resin matrix was cleverly solved, which helped the application of porous fillers in coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 This is the initial microscopic morphology of fly ash before treatment in one embodiment of the present invention;

[0031] Figure 2The microscopic morphology of the activated fly ash-based precursor in Example 2 of the present invention;

[0032] Figure 3 These are the test results of the coating samples in Example 1, Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 of the present invention after 500 hours of neutral salt spray test. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0034] Existing environmentally friendly anti-rust fillers have a single function and a complex process. They are difficult to protect metal substrates in harsh corrosive environments and cannot be widely used in environmentally friendly coatings such as water-based coatings. In addition, the interfacial wettability of commercially available environmentally friendly anti-rust fillers with resin matrices is poor, and they are prone to forming pore defects with the resin matrix, making it difficult to provide long-term anti-corrosion effects for metal substrates.

[0035] The present invention uses an alkali roasting method and a template pore-forming method to prepare a coexisting structure of a mesoporous metal oxide and activated fly ash in one step, and simultaneously dopes the two structures with metal elements to obtain an activated fly ash-based precursor. The activated fly ash-based precursor is secondary activated and aged using an activated dopant in an alkaline solution, and a zinc-doped fly ash-based ion exchange composite filler is formed through a crystallization process in a hydrothermal reactor, which has excellent ion exchange performance. Subsequently, the fly ash-based ion exchange composite filler is treated with a corrosion inhibitor and an ion modifier, and a multifunctional corrosion-inhibiting composite anticorrosive filler is prepared by a vacuum impregnation method.

[0036] A specific embodiment of the present invention provides a multi-effect corrosion-inhibiting functional anti-corrosion filler, including a fly ash-based composite multi-level structure, which is obtained by using fly ash as the main raw material at least through activation pore formation, hydrothermal doping and loading; wherein, the activation pore formation is at least a reaction of fly ash, an alkali activator, a metal oxide precursor, and a pore-forming agent as raw materials to obtain an activated fly ash-based precursor; the hydrothermal doping is a hydrothermal reaction of the activated fly ash-based precursor and a zinc source to obtain an ion exchange type composite filler; the loading is a composite of the ion exchange type composite filler with an ion modifier and a corrosion inhibitor modifier to obtain a fly ash-based composite multi-level structure.

[0037] Further, the pore forming agent includes one or more of polyethyleneimine, polyethylene glycol, sodium dodecyl sulfate and sodium alginate. The metal oxide precursor is selected from cerium nitrate, zinc nitrate and ferric nitrate. The alkaline activator includes one or both of sodium hydroxide and sodium carbonate. The ion modifier includes one or more of calcium oxide, calcium chloride, calcium nitrate and cerium nitrate. The corrosion inhibitor modifier includes one or both of triisopropanolamine and ethylenediaminetetraacetic acid. The zinc source is selected from zinc chloride and zinc nitrate.

[0038] In terms of the amount of raw materials used, the raw materials used for activated pore formation include fly ash, alkali activator, pore former and metal oxide precursor in a weight ratio of (15-40): (15-50): (2-6): (10-20); the raw materials used for hydrothermal doping include activated fly ash-based precursor, zinc source and water in a weight ratio of (15-40): (8-16): (20-50); the raw materials used for loading include ion exchange composite filler, ion modifier and corrosion inhibitor in a weight ratio of (3-8): (2-4): (1-2).

[0039] In addition, 150-400 parts by weight of fly ash, 150-500 parts by weight of alkali activator, 20-60 parts by weight of pore former, and 100-200 parts by weight of metal oxide precursor can be used to obtain an activated fly ash precursor through activation and pore formation; the activated fly ash precursor and 80-160 parts by weight of zinc source can be hydrothermally doped to obtain an ion exchange composite filler; the ion exchange composite filler can be compounded with 50-100 parts by weight of corrosion inhibitor and 50-100 parts by weight of ion modifier to obtain a fly ash-based composite multi-level structure.

[0040] Another specific embodiment of the present invention provides a method for preparing a multi-effect corrosion-inhibiting functionalized anticorrosive filler, comprising steps 1-3.

[0041] Step 1, using fly ash, pore-forming agent, metal oxide precursor and water as raw materials, and using an alkaline activator to perform alkali activation treatment and calcination treatment on the fly ash to prepare an activated fly ash-based precursor.

[0042] Specifically, fly ash, alkali activator, pore former, and metal oxide precursor are mixed uniformly in a container in a weight ratio of (15-40):(15-50):(2-6):(10-20), and a prepolymer with multiple structures coexisting is obtained after calcination. The calcination temperature is 700-900° C., and the calcination time is 1-12 hours.

[0043] During the preparation of activated fly ash-based precursors, the pore-forming agent not only plays a role in pore formation, but also forms a carbonized structure, namely an organic carbon layer, on the outer layer of the pore structure, thereby enhancing the wetting effect of the filler on the resin matrix and improving the ion exchange performance of the material.

[0044] The metal oxide precursor provides the skeleton structure of the mesoporous metal oxide, and at the same time, its surface carries a large amount of metal ions. In addition, the skeleton structure is also the polymerization seed unit for forming ion exchange fillers in the subsequent crystallization process. The mesoporous oxide mainly composed of cerium oxide plays a passivation corrosion inhibition role. It carries a large amount of cerium ions and accelerates the formation of a dense passivation layer in which cerium oxide and γ-ferric oxide coexist through its own redox process, slowing down the corrosion rate.

[0045] In step 1, the alkaline activator and fly ash form a highly adsorbable zeolite material during the calcination process. This process destroys the fly ash structure and converts the silicon and aluminum elements inside the fly ash from metal oxide forms into corresponding ions, providing raw materials for the formation of molecular sieve-like substances in the next hydrothermal reaction. Metal oxide precursors and pore-forming agents form mesoporous metal oxides under the calcination atmosphere. By selecting cerium metal oxides and iron metal oxides with corrosion inhibition, a mesoporous metal oxide structure is constructed as a polymerization reaction site to provide raw materials in the subsequent hydrothermal process. In addition, mesoporous metal oxides may be generated on the surface and inside of the fly ash after alkali excitation, thereby forming an activated fly ash-based precursor.

[0046] Step 2: Using activated fly ash-based precursor, activated dopant and water as raw materials, a hydrothermal reaction is carried out to prepare an ion exchange composite filler.

[0047] Specifically, an activated fly ash-based precursor, an activated dopant and water are mixed in a ratio of (15-40): (8-16): (20-50), and a hydrothermal reaction is carried out at 80-120° C. for 2-24 hours to form a corrosion-inhibiting functional filler with a multi-level structure coexisting and a strong cation exchange property.

[0048] In step 2, after the treatment in step 1, the original structure of the fly ash is destroyed. After the treatment, in addition to the metal oxide, there is also a porous fly ash structure or a zeolite fly ash structure inside, or there are both a porous fly ash structure and a zeolite fly ash structure, and there are also free silicon ions and aluminum ions. Under the action of the hydrothermal reaction, the silicon ions and the aluminum ions will form a molecular sieve-like structure with strong ion exchange performance, and similar A-type molecular sieves, X-type molecular sieves, and Y-type molecular sieves may be formed. The metal oxide, porous fly ash structure, and zeolite fly ash structure formed in step 1 will serve as molecular sieve polymerization sites in step 2 to form a fly ash-based ion exchange composite filler, which has the passivation characteristics of ion exchange anti-rust pigments and cathode passivation effects such as cerium oxide, and zinc is introduced in step 2. Zinc is atomically doped into the formed molecular sieve-like structure, which can enhance the ion exchange performance, and zinc can also be used as a sacrificial anode method to protect the metal from being corroded by the active metal in the corrosion, thereby slowing down the corrosion process.

[0049] Step 3, using the ion exchange composite filler, ion modifier, and corrosion inhibitor modifier as raw materials, performing a one-pot mixing reaction, and then vacuum impregnating, to obtain a multi-effect corrosion-inhibiting functional anticorrosive filler.

[0050] Specifically, fly ash-based ion exchange composite filler, ion modifier, and corrosion inhibitor modifier are mixed in a one-pot method at (3-8): (2-4): (1-2), and a proper amount of water is added. The mixture is stirred at 25 to 90° C., and a multi-effect corrosion-inhibiting functional anticorrosive filler is formed through rotary evaporation and vacuum impregnation processes.

[0051] The modification process of ion modifiers and corrosion inhibitor modifiers includes ion exchange process, organic grafting modification process and vacuum impregnation physical loading process. The calcium ions loaded by the multi-effect corrosion inhibition functional anticorrosive filler and the slightly soluble self-passivated silicate structure act as passivating corrosion inhibitors, which slow down the corrosion process by forming a passivation film on the filler itself and the metal substrate.

[0052] The corrosion inhibitor modifier is vacuum impregnated in the multi-effect corrosion inhibitor functional anti-corrosion filler to form an organic structure with a chelating effect, which forms a chelating complex with the iron ions generated during the corrosion process of the metal substrate, and is deposited on the metal substrate or fills the corrosion pores to slow down the corrosion process.

[0053] In step 3, Ca 2+ and Ce 3+ Loaded into fly ash-based ion exchange composite filler, different from step 1, the mesoporous metal oxide prepared in step 1 is in the form of oxide. 3+ and Ce 4+ , during the corrosion process, through its own redox characteristics (Ce 4+ →Ce 3+ ), slowing down the corrosion process; while in step 3, only Ce is loaded by utilizing the cation exchange characteristics 3+ , Ce 3+ As the raw material of passivation film in subsequent reaction process.

[0054] Another specific embodiment of the present invention provides a multi-effect corrosion-inhibiting and anti-corrosion coating, including the multi-effect corrosion-inhibiting functionalized anti-corrosion filler.

[0055] The present invention is further described in detail below in conjunction with specific embodiments.

[0056] Example 1

[0057] The multi-effect corrosion inhibition functional anticorrosive filler is prepared by the following scheme:

[0058] In parts by weight, 200 parts of fly ash, 250 parts of sodium hydroxide, 20 parts of polyethylene glycol, 10 parts of sodium alginate and 100 parts of cerium nitrate are mixed evenly and ground for 20 minutes. The particle size of the material after grinding is 800-1000 μm, and then calcined in a muffle furnace at 800° C. for 2 hours to obtain an activated fly ash-based precursor.

[0059] 100 parts of activated fly ash-based precursor, 100 parts of deionized water, and 20 parts of zinc chloride were mechanically stirred for 30 minutes, then aged at 80°C for 5 hours, and then hydrothermally reacted at 110°C for 6 hours. After crystallization, the fly ash-based ion exchange composite filler was prepared by gradually washing and drying.

[0060] 100 parts of fly ash-based ion exchange composite filler, 10 parts of calcium chloride, 10 parts of calcium oxide, 15 parts of cerium nitrate, and 30 parts of triisopropanolamine were stirred for 30 minutes, ultrasonically vibrated for 20 minutes, and then rotary evaporated and vacuum dried to form a multi-effect corrosion-inhibiting functional anticorrosive filler.

[0061] Example 2

[0062] The multi-effect corrosion inhibition functional anticorrosive filler is prepared by the following scheme:

[0063] In parts by weight, 400 parts of fly ash, 100 parts of sodium hydroxide, 150 parts of sodium carbonate, 15 parts of polyethylene glycol, 15 parts of sodium dodecyl sulfate, 100 parts of cerium nitrate and 30 parts of ferric nitrate are mixed evenly and ground for 20 minutes. The particle size of the material after grinding is 800-1000 μm, and then calcined in a muffle furnace at 900° C. for 6 hours to obtain an activated fly ash-based precursor.

[0064] 100 parts of activated fly ash-based precursor, 100 parts of deionized water, and 20 parts of zinc chloride were mechanically stirred for 30 minutes, then aged at 90°C for 6 hours, and then hydrothermally reacted at 90°C for 12 hours. After crystallization, the fly ash-based ion exchange composite filler was prepared by gradually washing and drying.

[0065] 50 parts of fly ash-based ion exchange composite filler, 5 parts of calcium chloride, 5 parts of calcium nitrate, 10 parts of cerium nitrate, and 20 parts of ethylenediaminetetraacetic acid were stirred for 30 minutes, ultrasonically vibrated for 20 minutes, and then rotary evaporated and vacuum dried to form a multi-effect corrosion-inhibiting functional anti-corrosion filler.

[0066] Comparative Example 1

[0067] The multi-effect corrosion inhibition functional anticorrosive filler is prepared by the following scheme:

[0068] In parts by weight, 300 parts of fly ash, 100 parts of sodium hydroxide, 150 parts of sodium carbonate, 100 parts of cerium nitrate and 30 parts of ferric nitrate are mixed evenly and ground for 20 minutes. The particle size of the material after grinding is 800-1000 μm, and then calcined in a muffle furnace at 750° C. for 8 hours to obtain an activated fly ash-based precursor.

[0069] 50 parts of activated fly ash-based precursor, 50 parts of deionized water, and 20 parts of zinc chloride were mechanically stirred for 30 minutes, then aged at 80°C for 6 hours, and then hydrothermally reacted at 100°C for 12 hours. After crystallization, the fly ash-based ion exchange composite filler was prepared by gradually washing and drying.

[0070] 50 parts of fly ash-based ion exchange composite filler, 5 parts of calcium chloride, 5 parts of calcium oxide, 5 parts of cerium nitrate, 20 parts of ethylenediaminetetraacetic acid, and 5 parts of triisopropanolamine were stirred for 60 minutes, and then rotary evaporated and vacuum dried to form a multi-effect corrosion-inhibiting functional anti-corrosion filler.

[0071] Comparative Example 2

[0072] The multi-effect corrosion inhibition functional anticorrosive filler is prepared by the following scheme:

[0073] In parts by weight, 200 parts of fly ash, 100 parts of sodium hydroxide and 50 parts of sodium carbonate were mixed evenly and ground for 20 minutes. The particle size of the material after grinding was 800-1000 μm, and then calcined in a muffle furnace at 900° C. for 6 hours to obtain an activated fly ash-based precursor.

[0074] 100 parts of activated fly ash-based precursor, 50 parts of deionized water, and 10 parts of zinc chloride were mechanically stirred for 30 minutes, then aged at 60°C for 6 hours, and then hydrothermally reacted at 105°C for 12 hours. After crystallization, the fly ash-based ion exchange composite filler was gradually washed and dried.

[0075] 100 parts of fly ash-based ion exchange composite filler, 15 parts of calcium nitrate, 5 parts of cerium nitrate, and 10 parts of ethylenediaminetetraacetic acid were stirred for 30 minutes, ultrasonically vibrated for 20 minutes, and then rotary evaporated and vacuum dried to form a multi-effect corrosion-inhibiting functional anticorrosive filler.

[0076] Comparative Example 3

[0077] The multi-effect corrosion inhibition functional anticorrosive filler is prepared by the following scheme:

[0078] In parts by weight, 300 parts of fly ash, 250 parts of sodium hydroxide, 20 parts of polyethylene glycol, 10 parts of sodium alginate, 50 parts of cerium nitrate, and 50 parts of ferric nitrate are mixed evenly and ground for 30 minutes. The particle size of the material after grinding is 800-1000 μm, and then calcined in a muffle furnace at 850° C. for 2 hours to obtain an activated fly ash-based precursor.

[0079] 100 parts of activated fly ash-based precursor and 100 parts of deionized water were mechanically stirred for 30 minutes, then aged at 80°C for 5 hours, and then hydrothermally reacted at 110°C for 6 hours. After crystallization, the fly ash-based ion exchange composite filler was prepared by gradually washing and drying.

[0080] 100 parts of fly ash-based ion exchange composite filler, 20 parts of calcium chloride, 15 parts of cerium nitrate and 30 parts of triisopropanolamine were stirred for 60 minutes, and then rotary evaporated and vacuum dried to form a multi-effect corrosion-inhibiting functional anticorrosive filler.

[0081] Comparative Example 4

[0082] The multi-effect corrosion inhibition functional anticorrosive filler is prepared by the following scheme:

[0083] In parts by weight, 150 parts of fly ash, 150 parts of sodium hydroxide, 50 parts of sodium carbonate, 15 parts of polyethylene glycol, 25 parts of sodium dodecyl sulfate, 50 parts of cerium nitrate, and 50 parts of ferric nitrate are mixed evenly and ground for 30 minutes. The particle size of the material after grinding is 800-1000 μm, and then calcined in a muffle furnace at 850° C. for 12 hours to obtain an activated fly ash-based precursor.

[0084] 100 parts of activated fly ash-based precursor, 150 parts of deionized water, and 30 parts of zinc chloride were mechanically stirred for 30 minutes, then aged at 70°C for 6 hours, and then hydrothermally reacted at 120°C for 3 hours. After crystallization, the fly ash-based ion exchange composite filler was prepared by gradually washing and drying.

[0085] 50 parts of fly ash-based ion exchange composite filler, 5 parts of calcium chloride, 5 parts of calcium nitrate, and 10 parts of cerium nitrate were stirred for 30 minutes, ultrasonically vibrated for 30 minutes, and then rotary evaporated and vacuum dried to form a multi-effect corrosion-inhibiting functional anti-corrosion filler.

[0086] Comparative Example 5

[0087] The multi-effect corrosion inhibition functional anticorrosive filler is prepared by the following scheme:

[0088] In parts by weight, 400 parts of fly ash, 15 parts of polyethylene glycol, 15 parts of sodium dodecyl sulfate, 100 parts of cerium nitrate, and 30 parts of ferric nitrate are mixed evenly and ground for 20 minutes. The particle size of the material after grinding is 800-1000 μm, and then calcined in a muffle furnace at 900° C. for 6 hours to obtain an activated fly ash-based precursor.

[0089] 100 parts of activated fly ash-based precursor, 100 parts of deionized water, and 20 parts of zinc chloride were mechanically stirred for 30 minutes, then aged at 90°C for 6 hours, and then hydrothermally reacted at 90°C for 12 hours. After crystallization, the fly ash-based ion exchange composite filler was prepared by gradually washing and drying.

[0090] 50 parts of fly ash-based ion exchange composite filler, 5 parts of calcium chloride, 5 parts of calcium nitrate, 10 parts of cerium nitrate, and 20 parts of ethylenediaminetetraacetic acid were stirred for 30 minutes, ultrasonically vibrated for 20 minutes, and then rotary evaporated and vacuum dried to form a multi-effect corrosion-inhibiting functional anti-corrosion filler.

[0091] The multi-effect corrosion-inhibiting functional anti-corrosion fillers in the above-mentioned embodiments and comparative examples are all prepared by the following scheme when preparing anti-corrosion and weather-resistant coatings. 50 parts by weight of epoxy resin, 30 parts by weight of polyamide, 15 parts by weight of deionized water and 15 parts by weight of propylene glycol methyl ether are mixed evenly by a high-speed disperser, 20 parts by weight of multi-effect corrosion-inhibiting functional anti-corrosion fillers are added thereto, stirred evenly, and the coating is sprayed on the surface of the metal substrate by an air pump spraying method, and a coating is formed after curing. Epoxy resin and polyamide are both conventional commercial products. When the multi-effect corrosion-inhibiting functional anti-corrosion fillers in the embodiments and comparative examples are used to prepare anti-corrosion and weather-resistant coatings, the epoxy resin and polyamide used are of the same type.

[0092] Performance Test:

[0093] (1) Anticorrosion Test: The coating samples formed in each embodiment and each comparative example were placed in a 3.5% NaCl solution for electrochemical impedance spectroscopy (EIS) test. The coating was tested for electrochemical impedance spectroscopy using a three-electrode system. The test frequency range was 100 kHz to 0.01 Hz. A 20 mV sinusoidal disturbance signal was applied to the sample. The test area of ​​the sample was 7.069 cm 2 The main test data are shown in Table 1. The EIS test results after immersion in 3.5% NaCl solution for 60 days are shown in Figure 3 shown.

[0094] Table 1 EIS test data

[0095] sample <![CDATA[Low-frequency impedance modulus (Ω·cm 2 )]]> Number of time constants Example 1 <![CDATA[6.69×10 10 ]]> 1 Example 2 <![CDATA[7.66×10 10 ]]> 1 Comparative Example 1 <![CDATA[3.77×10 8 ]]> 1 Comparative Example 2 <![CDATA[6.28×10 9 ]]> 2 Comparative Example 3 <![CDATA[9.56×10 7 ]]> 3 Comparative Example 4 <![CDATA[1.88×10 8 ]]> 2 Comparative Example 5 <![CDATA[4.25×10 7 ]]> 2

[0096] (2) Conventional test: The adhesion of the samples was tested by the pull-off method and the cross-cut test. The corrosion resistance of the samples was tested by the neutral salt spray test. The test results are shown in Table 2.

[0097] Table 2 Conventional performance test data

[0098]

[0099]

[0100] Referring to Table 1 and Table 2, we can draw the following conclusions:

[0101] The samples of Example 1 and Example 2 exhibited higher impedance moduli at low frequencies, and their values ​​were 6.69×10 10 Ω·cm 2 and 7.66×10 10 Ω·cm 2 The higher impedance modulus can reflect the compactness of the coating to a certain extent, indicating that there are fewer pores at the interface between the filler and the resin in the coating. In comparison, the impedance modulus of the comparative samples in the EIS test is lower than that of the embodiment, which is due to the properties of the filler itself.

[0102] Taking the impedance modulus of the sample in Example 2 as the reference standard, the impedance modulus of the sample in Comparative Example 1 is 3.77×10 8 Ω·cm 2 , the impedance modulus decreased significantly. In the preparation process of the sample of comparative example 1, no pore-forming agent was added, resulting in the absence of mesopores in the prepared oxide structure, which reduced the material's loading capacity for corrosion-inhibiting ions and reduced the material's reactive sites, resulting in a decrease in the anti-corrosion performance of the coating. In addition, after the pore-forming agent forms pores, it will construct an organic carbon structure in the material's mesopores, which can also improve the material's interface wettability.

[0103] Taking the impedance modulus of the sample in Example 2 as the reference standard, the impedance modulus of the sample in Comparative Example 2 is 6.28×10 9 Ω·cm 2 , the impedance modulus of the sample is lower than that of the standard sample. There is no metal oxide structure inside the filler, and its performance is between the sample of Example 2 and the sample of Comparative Example 1. This is because the anti-corrosion effect of the functional filler is based on the corrosion-inhibiting element, which also shows that the non-mesoporous metal oxide structure is not helpful for the cation exchange performance of the material.

[0104] Taking the impedance modulus of the sample in Example 2 as the reference standard, the impedance modulus of the sample in Comparative Example 3 is 9.56×10 7 Ω·cm 2, the impedance modulus value is relatively low. In the synthesis process of ion exchange filler, the scheme does not add a zinc source, i.e. zinc chloride, and there is no zinc atom doping inside the prepared ion exchange structure, which greatly reduces the ion exchange performance of the material, resulting in a reduction in the loading amount of corrosion-inhibiting ions (calcium ions and cerium ions) in the subsequent cation exchange process. And the final filler prepared in the embodiment includes a zinc-doped ion exchange structure, and zinc atom doping can enhance the activity of the material. It is analyzed that holes can be generated after doping, which can increase the active sites of cation exchange. In addition, the zinc element is introduced in the form of doping to determine the presence of elemental zinc in the structure, which gives the material a new corrosion inhibition effect, i.e. the cathodic protection method of sacrificial anodes, which is one of the reasons why the corrosion inhibition effect of the embodiment samples is excellent.

[0105] Taking the impedance modulus of the sample in Example 2 as the reference standard, the impedance modulus of the sample in Comparative Example 4 is 1.88×10 8 Ω·cm 2 , the impedance modulus of the sample of comparative example 4 is lower. In the preparation process of the sample of comparative example 4, the sample did not undergo a cation exchange process and a corrosion inhibition ion modification process, and there were fewer corrosion inhibition units in its structure, mainly because the cerium ions doped on the mesoporous oxide played a role in passivating the metal substrate, resulting in poor anti-corrosion effect of the sample.

[0106] Taking the impedance modulus of the sample in Example 2 as a reference standard, the impedance modulus of the sample in Comparative Example 5 is lower. In Comparative Example 5, no alkaline activator is added, resulting in the inability to effectively form a molecular sieve-like structure during the hydrothermal reaction, resulting in reduced corrosion inhibition of the filler.

[0107] From the results in Table 2, it can be seen that the neutral salt spray test results of the samples are very similar to the EIS results. Figure 3 The results of the salt spray resistance test of different samples are shown. From the results, it can be seen that the rust on the scratched part of the sample in Example 1 is very serious, which shows that the corrosion inhibition effect of the sample is poor. In the unscratched area of ​​the sample in Example 2, large areas of pitting corrosion occurred, which shows that the shielding performance of the coating is poor. The adhesion of the samples in Examples 3 and 4 is also poor, which shows that the mesoporous metal oxide in the composite structure plays a key role, especially in improving the interfacial wetting effect of the resin matrix in the coating.

[0108] Compared with the embodiment, the comparative example reduces the load of the corrosion inhibition unit by removing a certain raw material, resulting in a sharp decrease in the salt spray resistance of the sample, while the multi-effect corrosion inhibition functionalized anti-corrosion filler in the embodiment slows down the degree of damage to the coating by the corrosive medium under a variety of action mechanisms. In the final multi-effect corrosion inhibition functionalized anti-corrosion filler, calcium ions and cerium ions that can passivate the metal substrate are present at the same time, which form a new passivation film on the metal substrate to reduce the lateral diffusion of the corrosive medium. In addition, there is a carbonized structure inside the final multi-effect corrosion inhibition functionalized anti-corrosion filler, which improves the interfacial compatibility between the loose porous filler and the resin matrix, making the interior of the coating denser, thereby improving the adhesion of the coating to the metal substrate. It can also be seen from the cross-hatch test and the pull-off adhesion test that the samples prepared in the embodiment all show strong bonding strength.

[0109] As one of the synthetic raw materials for multi-effect corrosion inhibition functional anti-corrosion fillers, the microscopic morphology of fly ash is very important. During the formation process, fly ash is calcined at a high temperature of thousands of degrees, and its properties are very stable. Figure 1 The original structure of fly ash is spherical and irregular. In the sample preparation process, the initial structure of fly ash is destroyed by using alkaline activator, mesoporous metal oxide precursor and pore-forming agent under high temperature treatment, and the reaction sites inside the fly ash are released to the maximum extent. The microscopic morphology of the activated fly ash-based precursor after treatment is as follows: Figure 2 shown.

[0110] In the preparation process of the embodiments, the preparation process of the samples is very important. In the fly ash alkali excitation process, the mesoporous metal oxide with enhanced corrosion inhibition function is cleverly introduced to increase the corrosion inhibition potential of the composite filler, and the corrosion inhibition ions and carbonized structures that are helpful for corrosion protection are simultaneously introduced therein. Subsequently, in the hydrothermal crystallization process of the composite filler, the two structures are used as polymerization sites in the crystallization process of the composite filler, and the zinc element is cleverly introduced to prepare a doped ion exchange corrosion inhibition filler with sacrificial anode characteristics. Subsequently, in the preparation process of the final multi-effect corrosion inhibition functionalized anti-corrosion filler, the cation exchange process and the organic-inorganic functionalization process of the composite filler are compounded to prepare an excellent and effective corrosion inhibition filler to help the coating enhance the corresponding anti-corrosion effect.

[0111] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0112] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A multi-effect corrosion inhibition functional anticorrosive filler, characterized in that: It includes a fly ash-based composite multi-level structure, which is obtained by using fly ash as the main raw material through at least activation pore formation, hydrothermal doping and loading; The activated pore-forming step is to react fly ash, alkaline activator, metal oxide precursor and pore-forming agent as raw materials to obtain an activated fly ash-based precursor; Hydrothermal doping is to obtain ion exchange composite fillers by hydrothermal reaction of activated fly ash-based precursor and zinc source; The load is an ion exchange type composite filler, an ion modifier and a corrosion inhibitor modifier to obtain a fly ash-based composite multi-level structure.

2. The multi-effect corrosion inhibition functional anticorrosive filler according to claim 1, characterized in that: The raw materials used for activation and pore formation include fly ash, alkali activator, pore forming agent and metal oxide precursor in a weight ratio of (15-40): (15-50): (2-6): (10-20).

3. The multi-effect corrosion inhibition functional anticorrosive filler according to claim 1, characterized in that: The raw materials used for hydrothermal doping include an activated fly ash-based precursor, a zinc source and water in a weight ratio of (15-40): (8-16): (20-50).

4. The multi-effect corrosion inhibition functional anticorrosive filler according to claim 1, characterized in that: The raw materials used for loading include ion exchange type composite filler, ion modifier and corrosion inhibition modifier in a weight ratio of (3-8): (2-4): (1-2).

5. The multi-effect corrosion inhibition functional anticorrosive filler according to claim 1, characterized in that: The metal oxide precursor is selected from cerium nitrate, zinc nitrate and iron nitrate.

6. The multi-effect corrosion inhibition functionalized anticorrosive filler according to claim 1, characterized in that: The zinc source is selected from zinc chloride and zinc nitrate.

7. The multi-effect corrosion inhibition functional anticorrosive filler according to claim 1, characterized in that: The ion modifier is selected from calcium oxide, calcium chloride, calcium nitrate and cerium nitrate.

8. The multi-effect corrosion inhibition functional anticorrosive filler according to claim 1, characterized in that: The corrosion inhibitor modifier is selected from triisopropanolamine and ethylenediaminetetraacetic acid.

9. A method for preparing the multi-effect corrosion-inhibiting functional anticorrosive filler according to any one of claims 1 to 8, characterized in that: The steps include: S1, using fly ash, a pore-forming agent, a metal oxide precursor, and water as raw materials, and using an alkaline activator to perform an alkali activation treatment on the fly ash to prepare an activated fly ash-based precursor; S2, using an activated fly ash-based precursor, a zinc source, and water as raw materials to perform a hydrothermal reaction to prepare an ion exchange composite filler; S3. Using ion exchange composite fillers, ion modifiers and corrosion inhibitor modifiers as raw materials, a one-pot mixing reaction is carried out, and then vacuum impregnation is performed to obtain multi-effect corrosion inhibition functional anticorrosive fillers.

10. A multi-effect corrosion inhibition and anticorrosion coating, characterized in that: It comprises the multi-effect corrosion-inhibiting functionalized anticorrosive filler as described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Calcium-type zeolite-based imidazoline corrosion inhibitor as well as preparation method and application thereof

    CN108383408A

  • Mining activated fly ash composite colloid fire preventing and extinguishing material and preparation method thereof

    CN111632333A

  • Composite filler with anti-corrosion function as well as preparation method and application of composite filler

    CN117903620A

  • Corrosion-resistant and weather-resistant functional filler, preparation method thereof and corrosion-resistant and weather-resistant coating

    CN118772686A

  • AU2020100373A4